EVALUATION UTILIZATION FACILITIES FISH LANDING BASE (PPI) DUMAI OF DUMAI CITY RIAU PROVINCE - Sibarani, Elfrida; Zain, Jonny; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in March 2014, at the Fish Landing Base (PPI) Dumai Dumai Riau Province. The purpose of this study was to determine the level of utilization of the facilities available in the PPI Dumai.Facility utilization rates in the PPI Dumai consists of docks 237.19%, 140.98% of pond harbor area, harbor pool 58.75%, 47.54% auction room, fuel tanks 41.17%, 128.54% ice factory and 144.65% fresh water tank. Where the evaluation of the utilization of the facilities in 2014 is increasing compared to the use of the facilities in 2005.Keyword : Evaluation, facilities, fish landing bases